Ambient PM2.5 Transport in Bandar Lampung City: HYSPLIT Model and Meteorological Profile - Mustaqiman, Aulia Nur; Umar, Yasa Palaguna; Gustinasari, Kiki; Irawandani, Tia Dwi; Prayogo, Wisnu (Brawijaya University, 2024)
ABSTRACT Particulate Matter (PM2.5) is a hazardous air pollutant commonly found in urban areas, where emissions from transportation, industry, and fuel combustion significantly contribute to its concentration, posing serious risks to human health, air quality, and ecosystems. With rapid urbanization (1,073,451 people), transportation activities, and industrial growth, Bandar Lampung faces high PM2.5 concentrations from January to December 2023, up to 10.6 times the WHO threshold limit. This study analyzes the influence of daily meteorological conditions, such as wind speed, humidity, and temperature inversion, on the accumulation of PM2.5 pollutants in Bandar Lampung in 2023, focusing on August as the period with the highest pollution index (ISPU 155). This study utilizes the HYSPLIT application, which analyzes the sources and transport of PM2.5 pollutants based on wind direction. The HYSPLIT model results indicated that pollutants originate from the southeast at an altitude of 500 m and exhibit a more complex pattern at higher altitudes. Low wind speed (2.6 m/s) and low humidity (69%) during the month influenced the accumulation of PM2.5, reaching 53.6 µg/m³, exceeding the national threshold by 10.6 times. This study provided spatial information to support PM2.5 pollution mitigation efforts in Bandar Lampung by using the HYSPLIT model. Keywords: Bandar Lampung, HYSPLIT, meteorology, PM2.5, wind speed